Pengembangan Ekowisata Hutan Mangrove di Pantai Tirang, Kecamatan Tugurejo, Kota Semarang - Joel Stephen; Suryono Suryono; Agus Indarjo (Universitas Diponegoro, 2026)
The mangrove forest at Tirang Beach, Tugurejo District, Semarang City, is a mangrove conservation area utilized as a tourist destination. However, the mangrove forests in Semarang City face various threats, such as coastal abrasion, tidal flooding, and declining water quality. These coastal environmental dynamics have the potential to threaten the sustainability of mangrove ecotourism. Therefore, strategies are needed to manage the potential of mangrove forests as sustainable tourist destinations. This study aims to analyze the level of suitability and carrying capacity of mangrove ecotourism, as well as to formulate development strategies for mangrove forest tourism at Tirang Beach. The research was conducted from July to August at Tirang Beach, Tugurejo District, Semarang City. The research method used was a survey method through direct field observation and interviews with stakeholders. Observation station locations and respondents were determined using purposive sampling. The results indicate that the mangrove ecotourism area at Tirang Beach is supported by various tourism facilities, such as gazebos, food stalls, photo spots, a musala, and toilets. The Mangrove Tourism Suitability Index (IKW) was found to be 72.22%, categorized as quite suitable, while the Beach Tourism Suitability Index was 85.29%, which falls into the very suitable category. The maximum tourism carrying capacity was recorded at 314 visitors for an area of 11,650 m² with a four-hour visitation period. Tourism development at Tirang Beach can be pursued through infrastructure improvements, the establishment of local regulations, and the design of promotional strategies to enhance its tourist appeal. In addition, mangrove ecotourism development should focus on preparing a blueprint as a management concept based on education and on preparing human resources for its management. Hutan mangrove di Pantai Tirang, Kecamatan Tugurejo, Kota Semarang, merupakan kawasan konservasi bakau yang dimanfaatkan sebagai destinasi wisata. Akan tetapi hutan mangrove di Kota Semarang menghadapi berbagai ancaman, seperti abrasi pantai, banjir pasang, serta penurunan kualitas perairan. Dinamika lingkungan pesisir tersebut berpotensi mengancam keberlanjutan ekowisata mangrove. Oleh karena itu, diperlukan strategi pengelolaan potensi hutan mangrove sebagai destinasi wisata yang berkelanjutan. Penelitian ini bertujuan untuk menganalisis tingkat kesesuaian dan daya dukung ekowisata mangrove, serta merumuskan strategi pengembangan wisata hutan mangrove di Pantai Tirang. Penelitian dilaksanakan pada bulan Juli hingga Agustus di Pantai Tirang, Kecamatan Tugurejo, Kota Semarang. Metode penelitian yang digunakan adalah metode survei melalui observasi langsung di lapangan serta wawancara dengan para pemangku kepentingan (stakeholder). Penentuan stasiun pengamatan dan responden dilakukan menggunakan metode purposive sampling. Hasil penelitian menunjukkan bahwa kawasan ekowisata mangrove di Pantai Tirang telah didukung oleh berbagai fasilitas penunjang wisata, seperti gazebo, warung, spot foto, musala, dan toilet. Nilai Indeks Kesesuaian Wisata (IKW) mangrove sebesar 72,22% yang tergolong cukup sesuai, sedangkan Indeks Kesesuaian Wisata pantai sebesar 85,29% yang termasuk dalam kategori sangat sesuai. Daya dukung wisata maksimum tercatat sebanyak 314 wisatawan pada luasan 11.650 m² dengan waktu kunjungan selama empat jam. Pengembangan wisata Pantai Tirang dapat dilakukan melalui peningkatan infrastruktur, penyusunan aturan lokal, serta perancangan strategi promosi untuk meningkatkan daya tarik wisata. Selain itu, pengembangan ekowisata mangrove perlu diarahkan pada penyusunan cetak biru (blueprint) sebagai konsep pengelolaan ekowisata berbasis edukasi serta penyiapan sumber daya manusia dalam pengelolaannya.